Case Report: Could topical epidermal growth factor be considered a new therapy for skin injuries in premature infants? - Cossovel, F.; Marrazzo, F.; Nider, S.; Traunero, A.; Dussi, G.; Travan, L.; Cirino, M.; Zanon, D. (Frontiers in Pediatrics, 2024)
In this case report, we present the experience of a premature neonate born at 28 weeks of gestation who, following prolonged respiratory support, developed a pressure injury on the columella despite the implementation of all appropriate preventive techniques. This injury did not improve with standard therapies; therefore, it was necessary to apply a topical galenic therapy containing epidermal growth factor, resulting in complete healing of the lesion.